PWE-439 Delivering training in small intestinal capsule endoscopy: report of the inaugural uk regional deanery training day. (22nd June 2015) - Carr, R; Beale, A; Makins, RJ
Abstract : Introduction: Capsule endoscopy (CE) is widely used to image the small intestine. No formal training programme for CE exists in the UK, commercially run courses are available. The BSG CE group is developing formalised accreditation processes through which trainees will pass as part of their standard specialist training in gastroenterology, the level will depend on whether they wish to offer CE as a sub specialist interest. Regionally delivered training provides an opportunity to introduce CE, a valuable rsesource where training opportunities remain otherwise limited. We delivered the first regional training day in CE in January 2014 and describe its format and subsequent feedback. Method: Health Education South West (Peninsula and Severn Deaneries) run combined specialist training days for gastroenterology trainees. In January 2014, we delivered the first regional training day on CE in the UK. Trainees attended as part of their bi-monthly regional training programme. The teaching was provided by a consultant gastroenterologist with a wide experience in capsule endoscopy, supported by two colleagues. Following an introductory lecture, each trainee had access to an individual laptop loaded with interpretation software. 15 cases were studied throughout the day, demonstrating a wide variety of small intestinal pathology commonly seen with CE. The trainees were asked to give feedback at the end of the day and subsequently asked to complete a follow up online survey regarding their CE experiences during the following year. Results: 13 trainees attended (52%). Feedback on the day was graded as good/ very good (7/13) to excellent (4/13), 2 non responders. The use of individual laptops was particularly appreciated. 11 subsequently responded to the online survey (92%). All found the day useful. 3/11 (27%) intended to offer CE as a skill for Consultant applications. Prior to the session only 1 attendee had reported any CE, their training was adhoc informal departmental learning. This increased to 3 attendees at 1 year follow up (27%). Of those who had not reported any CE subsequently, 63% cited the reason as lack of the service at their current/ previous placement, whereas 38% had opportunity, but limited training time to do so. Trainee requests for CE after the training day increased by 27%, the majority of requests for iron deficiency anaemia. 56% of trainees felt a regional or national course such as this should be mandatory for all trainees and form part of core competence expected for CCT. Conclusion: Regionally delivered CE training as part of specialist training programme offers a unique opportunity for CE training in a group environment, until now only available commercially. UK trainess should have access to such training as part of their structured specialist training programme. Disclosure of interest: None Declared.